A Discourse Analysis of Education Memes on Instagram - Yosi Destira; Didin Nuruddin Hidayat; Alek Alek; Agus Sufyan (Loquen, 2021)
In the modern era, human has many ways to communicate, interact, and spread the idea. With the advancement of digital technologies, there are various media to convey messages; one of which is through internet memes. The present aims to investigate memes on Instagram through the lense of Critical Discourse Analysis. The objectives are to find out (1) the similarities and differences between Indonesian students and foreign students, (2) to analyze the relationship between pictures and text, and (3) to know the social function of memes. To seek answers, the researchers chose the ten best memes randomly from two Instagram accounts: Best Memes and Zona Mahasiswa” Furthermore, The memes have taken randomly depend on the researchers' needs. The study revealed no significant evidence of differences in education culture between Indonesia's and other countries memes. The results also indicated that the memes were able to serve as a means to communicate people’s activities to the readers. Further, the memes could be a compliment in communication and serve as a media for internet literacy development.